2007
DOI: 10.1021/tx700074n
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Diene Probes for Detection of Triplet Carbonyls in Biological Systems

Abstract: Electronically excited triplet carbonyls are formed during the oxidative degradation of polyunsaturated fatty acids, amino acids, and beta-dicarbonyl metabolites. Due to their long lifetime and high alkoxyl radical-like reactivity, triplet carbonyls may initiate deleterious reactions in biological systems. Here we study the quenching properties of conjugated dienes, specifically 2,4-hexadienoate (sorbate) and its alkyl ester, on triplet acetone generated chemically (thermolysis of tetramethyl-1,2-dioxetane) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 53 publications
1
46
0
7
Order By: Relevance
“…2 Furthermore, indisputable evidence of excited triplet carbonyls came from inhibition of dark CPDs in the presence of sorbate, a specific quencher of triplet energy. 9 Addition of 9,10-dibromoanthracene-2-sufonate (DBAS), which diverts the energy of excited triplets to luminescence, 9 also reduced the number of dark CPDs. Moreover, cell-free oxidation of synthetic melanin with peroxynitrite, or with hydrogen peroxide and peroxidase, generated ultraweak chemiluminescence.…”
mentioning
confidence: 99%
“…2 Furthermore, indisputable evidence of excited triplet carbonyls came from inhibition of dark CPDs in the presence of sorbate, a specific quencher of triplet energy. 9 Addition of 9,10-dibromoanthracene-2-sufonate (DBAS), which diverts the energy of excited triplets to luminescence, 9 also reduced the number of dark CPDs. Moreover, cell-free oxidation of synthetic melanin with peroxynitrite, or with hydrogen peroxide and peroxidase, generated ultraweak chemiluminescence.…”
mentioning
confidence: 99%
“…The lifetime of triplet carbonyls is ~10 μs (24), so a signal persistent over the course of hours indicates ongoing creation. To test whether this triplet state is required for dark CPD, we added ethyl sorbate, a specific quencher of triplet states (26), to intact melanocytes after UVA exposure. We found that this treatment prevented production of dark CPD (Fig.…”
Section: Photochemical Pathwaymentioning
confidence: 99%
“…É interessante notar que espécies carbonílicas no estado triplete, produzidas na termólise de dioxetanos e dismutação de radicais alcoxilas e peroxilas, formadas com altos rendimentos durante a peroxidação lipídica e outras oxidações biológicas, têm sido negligenciadas na literatura apesar de, in vitro, terem exibido reatividade similar à de radicais alcoxila. 5,6 Espécies reativas são formadas continuamente durante os processos metabólicos -normais ou patogênicos -ou são provenientes de fontes exógenas físicas e químicas. Tais espécies atuam como mediadores da transferência de elétrons e em vários processos bioquímicos, 7 como a fagocitose, fenômeno em que espécies reativas de oxigênio, H 2 O 2, ClO − e 1 O 2 *, são produzidas para eliminar o agente agressor por oxidação.…”
Section: Introductionunclassified